The Formation of Deposits on the Walls of the Pores in the Filtering Process - Yu. A. Taran; A. V. Kozlov; A. L. Taran (Тонкие химические технологии)
The aim of the work is to consider the mechanism of clogging the pores of the filter unit by small particles from the flow of filtrate inside them. Theoretical ideas about the process of filtering with the deposition of small particles from the filtrate on the pore walls and attribution of its fundamentals to restructuring from the original structure to the final structure allow to describe the process of clogging the pores using well studied concepts of known processes with phase transformations (in particular, crystallization). Based on this analogy and the approach to the description of the transformation of the "old" structure into a "new" one in time, using experimental data and their processing we calculated the rate of nucleation of the sediment centers (ωnucl), the linear (υlin) and volumetric rates of sediment plaques growth in the pores of the filter unit at different values of the process driving force, at different pressure difference in the system, and at different concentrations of solid particles in the suspension. Interpolation and extrapolation dependences were obtained for analyzing the mechanisms of sediments formation and growth for determining and calculating these (ωnucl, υlin) rates. Using the concepts of nonequilibrium thermodynamics to assess the influence of the driving forces we studied their influence (changes in the concentration of solid particles in the filtrate suspension and pressure drop across the filtering layer) on the dynamics of the filtration process. Using the data obtained it is possible to find the degree of clogging of through pores, which determines the filtration conditions, the filter septum type, and the filter overall dimensions.